The Relationship of Students Metacognitive Self-Regulation With Their Speaking Ability At Unp - Yunesa, Arvan; Mairi, Salam (Journal of English Language Teaching, 2024)
This study investigates the correlation between UNP's English department students' metacognitive self-regulation and their speaking ability. This research explores whether students who exhibit higher levels of metacognitive self- regulation demonstrate better speaking ability than those with lower skills. Theresearcher employed a quantitative method using Pearson's correlation to measure the relationship between two variables: students' metacognitive self-regulation (independent variable, X) and their speaking ability (dependent variable, Y). The study population includes four classes of public speaking. A sample of 30 students choose with simple random sampling from classes NK2-2022, NK3-2022, NK4-2022, and NK5-2022 were selected. Tests for speaking ability and a survey to see the students' metacognitive self-regulation were conducted to assess the relationship between the two variables. This study's findings demonstrated a correlation — one that was validated by statistical examination of the data — between students' metacognitive self-regulation and speaking ability. It was revealed that there is a substantial association between students' metacognitive self-regulation and speaking ability. Furthermore, the research shows a positive correlation, indicating that improved metacognitive self-regulation is linked to better speaking ability. Statistical analysis supports this, with a significant p- value of 0.008.